2020
DOI: 10.1037/xge0000625
|View full text |Cite
|
Sign up to set email alerts
|

Beyond emotional similarity: The role of situation-specific motives.

Abstract: It is well established that people often express emotions that are similar to those of other group members. However, people do not always express emotions that are similar to other group members, and the factors that determine when similarity occurs are not yet clear. In the current project, we examined whether certain situations activate specific emotional motives that influence the tendency to show emotional similarity. To test this possibility, we considered emotional responses to political situations that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 118 publications
1
34
0
1
Order By: Relevance
“…Previous research has suggested that political affiliation can be predicted by the political figures that users follow (Bail et al, 2018;Barberá, 2015;Brady et al, 2017;Goldenberg et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has suggested that political affiliation can be predicted by the political figures that users follow (Bail et al, 2018;Barberá, 2015;Brady et al, 2017;Goldenberg et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Such analyses can be done in online experiments that allow large numbers of individuals to interact with each other (or not) in predesigned social networks from their home computers (Coman, Momennejad, Drach, & Geana, 2016). In addition to these methods, we can measure bursts of activity or synchronization on digital media (Alvarez et al, 2015; Garas, Garcia, Skowron, & Schweitzer, 2012; Goldenberg et al, 2020). Collective-level emergent properties can be connected with individual-level results of experiments by using agent-based modeling, an approach that has seen recent advances (Garcia & Rimé, 2019).…”
Section: Key Questions and Future Directionsmentioning
confidence: 99%
“…At the individual level, the magnitude of emotions is dependent on individuals' construal of relevant stimuli. When emotions are experienced in the presence of other people, they tend to increase in magnitude, either because of emotion contagion between people (Goldenberg et al, 2020) or because people are motivated to communicate their emotions to others ( Jakobs, Manstead, & Fischer, 2001). This often means that collective emotions are characterized by increased intensity when experienced along with other individuals.…”
Section: Emergent Properties Of Collective Emotionsmentioning
confidence: 99%
“…Importantly, we extended Experiment 1 in a couple ways. Mackie, 1986;Mackie & Cooper, 1984;Goldenberg et al, 2019) and assimilate their self-evaluations to similar others (Mussweiler, 2003a(Mussweiler, , 2003b.…”
Section: Resultsmentioning
confidence: 99%